Sports-specific adaptation of left ventricular muscle mass in athlete's heart. II: An echocardiographic study with 400-m runners and soccer players - Urhausen, A.; Monz,T.; Kindermann, W. (International Journal of Sports Medicine, 1996)
Regarding the influence of the left ventricular (LV) adaptation by sports-specific factors the supposed endurance training have so far been compared mainly to strength conditioning. In the present study we investigated the echocardiographic LV measurements of endurance-trained athletes in different kinds of endurance sports (running and ball games) by using matched-pair procedures. We examined 22 male soccer players (S) and 22 male 400-m runners (R) on a regional up to a national level with--each similar in pairs--the following body mass (S: 75.7 +/-5.0 kg; R: 75.2 +/- 5.6), body surface area (S: 1.97 +/- 0.09 m2; R: 1.98 +/- 0.09), fat-free body mass (S: 68.4 +/- 4.6 kg; R: 68.3 +/- 5.3) and individual anaerobic threshold as a criterion to determine the running endurance (S: 14.23 +/- 0.79 km.h-1; R: 14.25 +/- 0.80). The body dimensions-related heart volume (HV/lean body mass: S: 14.2 +/- 1.5 ml.kg-1; R: 13.4 +/- 1.0) as well as the absolute and body surface-related LV internal diameter (EDD: S: 55.0 +/- 3.8 mm; R: 52.7 +/- 3.3; EDD/body-surface area: S: 27.8 +/- 1.9 mm.m-2; R: 26.6 +/- 1.3) were measured significantly higher in S as compared to R (p < 0.05 and p < 0.01, respectively). In both groups, free LV wall thickness, enddiastolic diameter and LV muscle mass correlated significantly with the body dimensions (fat-free body mass: r = 0.42 - 0.48 - 0.56; p < 0.004, respectively). In conclusion, specific sport-related strain like frequent exercises in interval form (typical for ball games) and a different volume/intensity ratio could significantly influence the LV adaptation beside the endurance performance as well as constitutional and genetic factors.